Use of NaF-18-Positron Emission Tomography/Computed Tomography in the Detection of Bone Metastasis from Papillary Renal Cell Carcinoma - Carina Aparici; Aung Win (World Journal of Nuclear Medicine)
We present a case of a 60-year-old white male with a history of papillary renal cell carcinoma (PRCC) status postpartial nepherectomy. He was followed-up annually with abdominal computed tomography (CT) scans to monitor for tumor recurrence. A solitary metastatic bony lesion was detected by CT 4 years after partial nephrectomy and it was confirmed by NaF-positron emission tomography (PET)/CT and magnetic resonance imaging. He underwent external beam radiation therapy (XRT) for solitary metastasis to L1 vertebra. The L1 lesion was treated with XRT, which exhibited no fluorodeoxyglucose activity after the treatment. This is the first case report to mention the use of NaF-18-PET/CT in the detection of bone metastasis from PRCC. Our case once again emphasizes the usefulness of NaF-18-PET/CT in RCC follow-up.